2016
DOI: 10.1097/md.0000000000003734
|View full text |Cite
|
Sign up to set email alerts
|

IL-8 Alterations in HIV-1 Infected Children With Disease Progression

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 53 publications
3
13
0
Order By: Relevance
“…Increased IL-8 plasma levels in cancer patients predict increased disease severity [64][65][66][67]. Consistently, published data in HIV infection has shown that increased IL-8 levels correlate with mortality, reduced CD4 cell count and increased viral load [28][29][30][31][32][33]. In a study of HIV/tuberculosis coinfected patients, a direct association of plasma IL-8 levels was found with frequencies of granulocytes and their capacity to migrate in response to IL-8.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Increased IL-8 plasma levels in cancer patients predict increased disease severity [64][65][66][67]. Consistently, published data in HIV infection has shown that increased IL-8 levels correlate with mortality, reduced CD4 cell count and increased viral load [28][29][30][31][32][33]. In a study of HIV/tuberculosis coinfected patients, a direct association of plasma IL-8 levels was found with frequencies of granulocytes and their capacity to migrate in response to IL-8.…”
Section: Discussionsupporting
confidence: 62%
“…IL-8 is an important factor for the migration and activation of polymorphonuclear cells, which include PMN-MDSCs. In the context of HIV infection, IL-8 has been studied extensively and has been shown to be a marker of immune activation in HIV disease with relevance to polymorphonuclear cells [27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Also observed was a higher expression of CXCL8 in untreated HIV-1-infected progressors and cART nonresponders compared to long-term nonprogressors and cART responders, respectively. Furthermore, a negative correlation of plasma levels of CXCL8 with CD4 counts was found in HIV-1-infected cART-naive subjects, whereas the CXCL8 levels positively correlated with viral load in the cART-treated children (27). These observations suggest a strong link between CXCL8 through its proinflammatory action to viral replication and disease progression.…”
Section: Discussionmentioning
confidence: 77%
“…Disease progression in HIV-1 infection involves a complex set of interactions between viral and host factors leading to a chronic immune activation state. Inflammation has been shown to be a contributing factor, in addition to T cell activation, towards disease progression and mortality ( 13 ). In viremic individuals, it has long been recognized that viral replication may not solely be responsible for disease progression; immune activation status being an important determinant too ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The pediatric model affords several advantages for studying virus-host interactions, including the information on virus source and time of exposure ( 11 ). In infants who are exposed to HIV-1, innate immunity is of particular relevance in conferring protection since the adaptive immune system is still under development ( 12 , 13 ). There is a paucity of information on the interactions between innate and adaptive immune response in HIV-1 infection that influences disease progression in infected children.…”
Section: Introductionmentioning
confidence: 99%